HUBUNGAN KOMPETENSI PEDAGOGIK DAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN PROFESIONALITAS GURU DI PERGURUAN MUHAMMADIYAH CIPONDOH TANGERANG - Suhelmi Suhelmi; Suherman Suherman; Syadeli Hanafi (JTPPm (Jurnal Teknologi Pendidikan dan Pembelajaran) : Edutech and Intructional Research Journal, 2021)
The purpose of this study was to determine and analyze the relationship between pedagogic competence and principals' leadership with teacher professionalism. This type of research is a quantitative field research with a correlational approach. This research was conducted at the Cipondoh Muhammadiyah College, Tangerang. The population in this study were teachers at the Muhammadiyah College Cipondoh Tangerang with a total sample of 85 teachers. The results sH0wed that: 1) Based on the results of the analysis, it was concluded that there was a relationship between pedagogical competence and teacher professionalism at the Muhammadiyah College of Cipondoh Tangerang City, with rcount > rtable (0.284 > 0.213) and Sig value < value (0.000 < 0.05); 2) There is a relationship between the principal's leadership and teacher professionalism at the Cipondoh Muhammadiyah College, Tangerang City, with rcount > rtable (0.240 > 0.213) and Sig value < value (0.000 < 0.05); 3) There is a relationship between Pedagogic Competence and Principal Leadership together with teacher professionalism at the Cipondoh Muhammadiyah College, Tangerang City with an rcount > rtabel (0.329 > 0.213) and together the pedagogical competence and leadership of the principal contributed 10, 8% of the professionalism of teachers at the Cipondoh Muhammadiyah College, Tangerang City.Keywords: Pedagogic Competence, Principal Leadership, Teacher Professionalism